2011
DOI: 10.1016/j.yjmcc.2010.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of cartilage and bone-related proteins in pediatric and adult diseased aortic valves

Abstract: Approximately 5 million people are affected with aortic valve disease (AoVD) in the United States. The most common treatment is aortic valve (AoV) replacement surgery, however, replacement valves are susceptible to failure, necessitating additional surgeries. The molecular mechanisms underlying disease progression and late AoV calcification are not well understood. Recent studies suggest that genes involved in bone and cartilage development play an active role in osteogenic-like calcification in human calcific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
113
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(127 citation statements)
references
References 49 publications
12
113
1
Order By: Relevance
“…While positive SMαA expression may not always be necessary for VICs to transition to an osteoblast-like phenotype [10], it is often used to identify VICs undergoing calcification and is found in much higher amounts in diseased aortic valves [31]. Therefore, identification of this marker in 3D VIC cultures is essential.…”
Section: Discussionmentioning
confidence: 99%
“…While positive SMαA expression may not always be necessary for VICs to transition to an osteoblast-like phenotype [10], it is often used to identify VICs undergoing calcification and is found in much higher amounts in diseased aortic valves [31]. Therefore, identification of this marker in 3D VIC cultures is essential.…”
Section: Discussionmentioning
confidence: 99%
“…End-stage disease is characterized by the presence of calcific nodules at the hinge region of the AoV, underlying the pathology of CAVD [3]. In an effort to draw parallels between the progression of disease and the underlying molecular mechanisms, pediatric and adult diseased AoV were analyzed for markers of valve development and endochondral bone formation [7]. Activated VICs in both pediatric and adult valves have increased expression of valvulogenic markers Twist1, Msx2, and Sox9.…”
Section: Calcific Aortic Valve Disease (Cavd)mentioning
confidence: 99%
“…We have reported that pediatric and adult diseased valves are characterized by expression of markers of valve mesenchymal and chondrogenic progenitor cells, while adult diseased aortic valves express markers of osteogenic calcification [7]. We also have identified novel mouse models of calcific and myxomatous valve disease [8] that will be useful in determination of the underlying mechanisms driving disease and in development of pharmacologic-based therapies.…”
Section: Introductionmentioning
confidence: 99%
“…25 During aortic valve disease progression, both pediatric and adult diseased aortic valves express markers of chondrogenic cells, while adult diseased aortic valves express more mature osteogenic markers. 26 However, it is unclear what potency pediatric VIC possess, and controlling stable MSC differentiation toward pediatric VIC is important for longterm success of TEHV for pediatric applications.…”
Section: Introductionmentioning
confidence: 99%